Devising evidence-based strategies for progress towards zero-carbon energy at the country level: The by-production approach. (15th August 2023) - Shen, Zhiyang; Balezentis, Tomas
Abstract: The development of the sustainable energy systems is crucial for economic growth and climate change mitigation. This paper proposes a nonparametric approach based on the by-production technology comprising the economic and environmental sub-technologies. We consider both renewable and fossil energy in the analysis. This approach allows identifying the most relevant energy development strategies at the country level. We examine 42 countries from the OECD, B(R)ICS and ASEAN. The results indicate that most of the countries (23) need to exploit both the energy intensity and carbon factor (energy-mix) effects to ensure sustainable energy development, yet four countries also need to increase the use of the renewable energy in order to secure the economic growth. During 1990–2018, an upward trend for the CO2 emission shadow price is observed for the selected countries which suggests an improving environmental performance. The results of this study provide further guidelines for adopting effective market-oriented policy measures in the energy sector. Highlights: A Data Envelopment Analysis model is constructed to identify performance gaps. Both energy intensity and energy-mix adjustments are modelled. Double frontier model is used. The empirical study covers OECD, B(R)ICS and ASEAN countries. Most of the countries need to opt for combined energy strategies.